Voluntary approaches, the environment and the law: A Canadian perspective - Kernaghan Webb; Andrew Robert Morrison (Fondazione Eni Enrico Mattei (FEEM), 1997)
Where a firm, or group of firms, pledges voluntarily to adhere to a particular set of rules pertaining to environmental protection, there are significant legal ramifications. Indeed, voluntary code regimes often act as adjuncts to the legal system, with substantial legal effects, intended or not. Analysis suggests that regulatory approaches to environmental protection tend to be advantageous in terms of visibility, credibility, accountability, compulsory application to all, greater likelihood of rigorous standards being developed, cost spreading, and availability of a range of sanctions. However, regulatory approaches are often highly formal, expensive to operate, may foster adversarial relationships, are subject to jurisdictional constraints, and are difficult and costly to amend. In contrast, voluntary rule systems pertaining to the environment are generally more flexible, less costly, easier to establish and amend, have a broader jurisdiction, have a potential for the positive use of peer pressure and the internalization of responsibility, and are less formal. Typical negative aspects include, generally lower visibility, credibility, difficulty in applying the rules to free riders, a lower likelihood of developing rigorous standards, uncertain accountability to the public, and a more limited array of sanctions options. Despite their noncompulsory nature, voluntary codes can have significant legal implications, in contract or tort law. Failure to comply with a relevant code can be used to establish negligence. Significantly, the failure to comply with a particular code can weigh heavily against a company, even when the company did not consent to participate in the code. In addition, voluntary codes can be used by a company to demonstrate that they exercised due diligence in a civil or penal negligence case. Further, voluntary arrangements could run afoul of competition law if their agreements or standards decrease competition in the marketplace. The various legal ramifications of voluntary codes suggest that individuals, firms, non-governmental organizations and governments must thoroughly explore these implications before proceeding with such initiatives. It is possible to devise and operate voluntary codes which serve both the public and private interests concerned, but failure to properly consider the legal implications and act accordingly could potentially result in problems for all concerned.
Keywords: 330; Umweltrecht; Umweltmanagement; Selbstverpflichtung; Kanada